L’EduHub malaisien entre tradition et désirs de reconnaissance - Régis Machart; Fred Dervin (Cahiers de la Recherche sur l'Education et les Savoirs)
Malaysia is a popular destination for students from the Middle-East and North Africa (MENA) who represented 40% of international students in the country in 2010. For many politicians and a few researchers this flux appears to be related to ‘cultural’ and religious elements. But how do the students themselves justify this phenomenon? The article reviews first how Malaysian higher education developed in relation to internationality. Our second goal consists in examining how the Malaysian EduHub is conceptualised and discussed. If some students chose Malaysia as their preferred destination, many would prefer other destinations, thus questioning the argument that ‘cultural proximity’ is an important factor for incoming students to Malaysia – practical and financial arguments being more decisive.